Awareness and knowledge of insurance and Takaful in India: A survey on Indian insurance policy holders - Salman, Syed Ahmed; Abdul Rashid, Hafiz Majdi; Hassan, Rusni (Man In India, 2017)
India is a country with the second highest Muslim population after Indonesia and the second largest populated country in the world after China. Since 1818 during the colonization period, insurance was introduced in India. Nowadays, the Indian insurance industry is growing fast. Despite being the second largest Muslim populated country, there is no Takaful (Islamic insurance) products offered in India. Thus, this paper aims to examine the insurance policy holders’ awareness and knowledge of insurance and Takaful in India. The findings show that the non-Muslim insurance policy holders are not aware that insurance practice involves interest, uncertainty and gambling. Similarly, the majority of non-Muslims do not think that insurance practice should be prohibited based on their religious teachings. Interestingly, the majority of respondents have not heard about Takaful. On the contrary, the majority of Muslim know that insurance practices have interest, uncertainty and gambling, and at the same time they think that conventional insurance should be prohibited based on religious teachings. The majority of both Muslims and non-Muslim respondents believe that ethics is important in the insurance practice. It can be concluded that awareness and knowledge of Takaful in India is very low. It might be the main reason why Takaful has not been introduced in India yet